Bilayered Potassium Vanadate K0.5V2O5 as Superior Cathode Material for Na‐Ion Batteries. Issue 23 (30th October 2019) - Baddour‐Hadjean, Rita; Thanh Nguyen Huynh, Le; Batyrbekuly, Daureen; Bach, Stéphane; Pereira‐Ramos, Jean‐Pierre
Abstract: A bilayered potassium vanadate K0.5 V2 O5 (KVO) is synthesized by a fast and facile synthesis route and evaluated as a positive electrode material for Na‐ion batteries. Half the potassium ions can be topotactically extracted from KVO through the first charge, allowing 1.14 Na + ions to be reversibly inserted. A good rate capability is also highlighted, with 160 mAh g −1 at C/10, 94 mAh g −1 at C/2, 73 mAh g −1 at 2C and excellent cycling stability with 152 mAh g −1 still available after 50 cycles at C/10. Ex situ X‐ray diffraction reveals weak and reversible structural changes resulting in soft breathing of the KVO host lattice upon Na extraction–insertion cycles (Δ V / V ≈3 %). A high structure stability upon cycling is also achieved, at both the long‐range order and atomic scale probed by Raman spectroscopy. This remarkable behavior is ascribed to the large interlayer spacing of KVO (≈9.5 Å) stabilized by pillar K ions, which is able to accommodate Na ions without any critical change to the structure. Kinetics measurements reveal a good Na diffusivity that is hardly affected upon discharge. This study opens an avenue for further exploration of potassium vanadates and other bronzes in the field of Na‐ion batteries. Abstract : A stable host : Bilayered K0.5 V2 O5 (KVO), synthesized by a fast, facile and low‐cost solution route, is evaluated as a cathode material for Na‐ion batteries. The large interlayer spacing combined with pillar K + ions promotes remarkable Na intercalation properties, with high capacity (152 mAh g −1 after 50 cycles at C/10 in the 4–1.5 V range), fast diffusivity of Na + ions in the interlayer space, and good rate capability (73 mAh g −1 at 2C).